A graphene integrated Kapton based flexible and highly sensitive plasmonic sensor for uric acid sensing - Sagar Kumar Verma; Yadvendra Singh; Harish Subbaraman; Nirmala Kandadai (Sensors and Actuators Reports)
One of the most common natural waste products from diets high in purines is uric acid that is commonly filtered by human kidneys. Excessive consumption and delayed excretion of uric acid can disrupt blood uric acid levels. Abnormal variations in the normal uric acid level, which is less than 6.8 mg/dL, can lead to several health issues, including kidney stones and gout, etc. Available biosensors for uric acid detection have various issues such as low sensitivity, poor selectivity, shorter shelf life, and poor repeatability. Kretschmann configuration-based plasmonic sensors are prominent candidates for resolving the issues but the available plasmonic chips are expensive because of the involvement of special glass substrates, such as SF11 and BK7. This work mainly focuses on the replacement of SF11 glass sensing chips with a low-cost and flexible Kapton chip that shares the same refractive index as SF11, without compromising the sensor’s sensitivity. Moreover, to enhance the sensitivity of the Kapton based plasmonic chips, they were integrated with 1 – 3 layers of graphene. These graphene-integrated flexible (GiF) plasmonic chips were functionalized with uricase enzyme to develop molecule selective uric acid sensors for point-of-care detection. The developed GiF chips achieved a maximum sensitivity of 0.0810nm/μM and 0.0171nm/μM in the range 0 to 200μM, and 200 to 1000μM, respectively, with a limit of detection of 11.450μM for uric acid. Controlled experiments were also performed to demonstrate the repeatability, stability, and selectivity of the sensors. GiF SPR chip presents its strong potential in developing portable and wearable biosensors.